Nurses' Perspectives on Factors Affecting Patient Safety: A Qualitative Study - Marzieh Pazokian; Fariba Borhani (Mashhad University of Medical Sciences, 2017)
Patient safety is a global concern that involves all healthcare members, so that achieving a high level safe care is responsibility of all healthcare services, particularly nurses. This qualitative study aimed to describe nurses' perspectives on factors affecting patient safety. We recruited 32 nurses working in teaching hospitals by purposeful sampling method. Data were collected by semi-structured interviews, and transcripts were analyzed by conventional content analysis approach. Two themes were extracted from data analysis including "Patient-Centered Care" and "Organizational-Based Factors", and eight categories delineated from participants' experiences with regard to the patient safety. Based on the results, complexity of patient centered-care is an obstacle for implementation in practice. Therefore, educating nurses for focusing on patient interaction and cooperation is essential for achievement to proper care and improving quality of care.Furthermore, improving facilities and equipment, providing sufficient and efficient personnel by the executive director are necessary in effective clinical services.